The relationship between perfectionism, rumination, and academic procrastination among Chinese college students - Huang Jing; Sabariah Sharif; Chua Bee Seok (Penerbit UMS, 2025)
Academic procrastination has a significant impact on college students' academic performance and future employment prospects, making it an important issue to address. This study aimed to examine the effects of perfectionism and rumination on academic procrastination among college students. Additionally, the study explored the mediating role of rumination in the relationship between perfectionism and academic procrastination. A total of 460 students from four representative universities in Southwest China were surveyed using The Chinese Frost Multidimensional Perfectionism Scale (CFMPS,1991) Rumination Scale (RRS), and Academic Procrastination Scale (API). The scales demonstrated good reliability and validity. The study analyzed correlations and regression relationships among the variables and also investigated the mediating effect of rumination. The results indicated that perfectionism did not directly affect students' academic procrastination; instead, it influenced procrastination through rumination. Rumination fully mediated the relationship between perfectionism and academic procrastination.